A county-scale assessment of ecosystem health in the Three Gorges Reservoir area based on catastrophe theory - Xie, Wangying; Li, Yi; Zhao, Yiqiu; Chen, Ying; He, Jia; Wen, Chuanhao (Frontiers in Environmental Science, 2023)
The integrity and health of the ecosystem is the material basis for the common prosperity of different minority regions. Since the acceleration of social and economic growth in the 21st century, excessive demand has caused problems such as ecological imbalance, climate change, and environmental pollution. The unreasonable use of natural resources has gradually affected the balance between man and nature. On the basis of understanding and grasping the health characteristics and key elements of the ecosystem in the Three Gorges Reservoir area, starting from the four subsystems of environment, economy, society and management, this paper constructs an ecosystem health evaluation index system to comprehensively describe the ecosystem of the Three Gorges Reservoir area. health status. By using the catastrophe catastrophe theory to establish a multi-criteria evaluation model, it is intended to evaluate the health status of the ecosystem. Secondly, the catastrophe evolution method (CPM) was used to describe the overall change trend of the ecosystem in the Three Gorges Reservoir area from 2000 to 2016. The results show that with the development of economy and society and the further strengthening of environmental management, the strengthening of environmental management and climatic factors have led to the improvement of the ecosystem health in the Three Gorges Reservoir area year by year since 2000. At the same time, in order to further explore the factors affecting the health of the reservoir ecosystem, starting from climatic factors, the panel data was used to establish a model regression analysis, and the final conclusion was drawn: the average temperature, rainfall and sunshine hours have a significant impact on the ecosystem in the reservoir area.